Amblytropidia paranaensis n. sp., a new species of grasshopper (Orthoptera: Acrididae: Gomphocerinae) from Paraná State, Brazil, including new records, a distribution map and a key to the Brazilian’s species - Costa, Maria Kátia Matiotti Da; Nogueira, Thayla Melissa Gimenez; Prasniewski, Victor Mateus; Zefa, Edison; Szinwelski, Neucir (Zootaxa, 2023)
A new species of Amblytropidia Stål, 1873 (Orthoptera, Acrididae, Gomphocerinae), named Amblytropidia paranaensis n. sp., is delineated from the Três Barras do Paraná municipality, Paraná State, Brazil. Detailed morphological delineations, accompanied by illustrations highlighting key diagnostic traits of both male and female external genitalia, are provided. Amblytropidia paranaensis n. sp. is distinguished from its congeners by distinctive body coloration, particularly evident in the head and thorax regions, as well as larger-sized anchorae compared to anterior projections, and uniquely trilobated and sclerotized lophi. Moreover, this study offers insights into the species’ habitat preferences, documented occurrences, a distribution map, and an updated taxonomy key specific to Brazilian Amblytropidia species.